Antitubercular Triazines: Optimization and Intrabacterial Metabolism. Issue 2 (20th February 2020) - Wang, Xin; Inoyama, Daigo; Russo, Riccardo; Li, Shao-Gang; Jadhav, Ravindra; Stratton, Thomas P.; Mittal, Nisha; Bilotta, Joseph A.; Singleton, Eric; Kim, Thomas; Paget, Steve D.; Pottorf, Richard S.; et al.
Summary: The triazine antitubercular JSF-2019 was of interest due to its in vitro efficacy and the nitro group shared with the clinically relevant delamanid and pretomanid. JSF-2019 undergoes activation requiring F420 H2 and one or more nitroreductases in addition to Ddn. An intrabacterial drug metabolism (IBDM) platform was leveraged to demonstrate the system kinetics, evidencing formation of NO ⋅ and a des-nitro metabolite. Structure-activity relationship studies focused on improving the solubility and mouse pharmacokinetic profile of JSF-2019 and culminated in JSF-2513, relying on the key introduction of a morpholine. Mechanistic studies with JSF-2019, JSF-2513, and other triazines stressed the significance of achieving potent in vitro efficacy via release of intrabacterial NO ⋅ along with inhibition of InhA and, more generally, the FAS-II pathway. This study highlights the importance of probing IBDM and its potential to clarify mechanism of action, which in this case is a combination of NO ⋅ release and InhA inhibition. Graphical Abstract: Highlights: Optimization of an antitubercular agent afforded gains in solubility and plasma PK The triazines release intrabacterial NO ⋅ as the predominant mechanism of action The triazines/their intrabacterial metabolites also inhibit InhA and FAS-II pathway Abstract : Wang et al. disclose the optimization of a triazine antitubercular agent and probe its mechanism of action. They demonstrate the significance of studying intrabacterial drug metabolism. Through this approach and other methods, they evidence a novel mechanism involving NO ⋅ release and inhibition of the cell wall biosynthesis enzyme InhA.